Pinakatagong lihim ng simbahan [videorecording] - Calso, Tingting; Carolino, Ditsi; Institute on Church and Social Issues (Philippines). (Manila ICSI/ISO, 1993)
A video-documentary on the church in action after the Second Plenary Council. Reveals the social teachings of the church as lived by ordinary people in two basic ecclesial communities. Shows glimpses of life in Paco's slum area and in Bukidnon where the church struggles to protect the province's remaining forests.
VHS.
Tagapagsalaysay, Bodgie Pascua.
Keywords: Sociology, Christian (Catholic); Church and social problems -- Catholic Church. -- Philippines